FORMULASI DAN OPTIMASI TABLET FLOATING SALBUTAMOL SULFAT MENGGUNAKAN FACTORIAL DESIGN - , Wa Ode Sitti Zubaydah, S.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Salbutamol sulphate has a relatively short half-life (4 hours), with oral doses of 2-4 mg, with 3-4 times daily administration. Sustained-release formulation of salbutamol sulphate in a tablet dosage form is expected to reduce the frequency of drug use, produce more uniform serum concentrations with less fluctuation in peak through levels. The physical properties of tablets and drug release from tablets floating system are influenced by properties of matrix component, i.e. Ethyl cellulose (hydrophobic matrix), xanthan gum (free flowing, gelling agent), and sodium bicarbonate that reacts with gastric fluid to form CO2. The research was done with factorial design by using 3 components, i.e. ethyl cellulose (A), xanthan gum (B), and sodium bicarbonate (C), so that eight formula were obtained. The Optimization parameters of salbutamol sulphate sustained-release were drug content uniformity, floating lag time, first order kinetics of drug release (K of first order), and the DE360. Based on factorial design model, equations and contour plots were obtained, by which the optimum formula can be determined. Ethyl cellulose was the most dominant factor in increasing uniformity of content. Sodium bicarbonate is the dominant factor affecting to the floating lag time. Ethyl cellulose and xanthan gum increase the value of K-first order, while sodium bicarbonate is decrease it. Sodium bicarbonate is the most influential in reducing the DE360. Based on desirability value, optimum formula 17.58 mg of ethyl cellulose, 78.51 mg of xanthan gum, and 30 mg of sodium bicarbonate were obtained.